Modeling of light scattering in biotissue - Ivashko, P.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Different statistical modeling techniques of radiation propagation in epithelial tissue are considered. The two main approaches are: the modified classical Monte Carlo method for light propagation in turbid medium and the coherent inverse ray tracing method. The classical Monte Carlo method was modified to take into account polarization of propagating radiation and birefringence, which can occur due to tissues commonly found under epithelium. As a supplementary method, used in the paper was a modified version of the classical ray tracing technique, which takes into account phase of radiation during its propagation in tissue.